2015
DOI: 10.1111/ibi.12295
|View full text |Cite
|
Sign up to set email alerts
|

Secondary phytohaemagglutinin (PHA) swelling response is a good indicator of T‐cell‐mediated immunity in free‐living birds

Abstract: El phytohaemagglutinin (PHA) se prueba para medir la inmunidad adquirida y es uno de los métodos más utilizados; actualmente, está siendo debatido a raíz de los nuevos conocimientos sobre la compleja fisiología del proceso. Como respuesta secundaria reiterada a los mayores desafíos vinculados a los aumentos de los niveles de linfocitos T circulantes sería indicativo de una respuesta inmune mediada por células, se realizó por primera vez un experimento bajo condiciones naturales con repetidas PHA desafíos en li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Although data on immune response variables were not available for many species, we did find differences between males and females. The four immune assays analysed reflect innate immunity, except the PHA test that, if repeated more than once, also includes components of the adaptive immunity 85 . The PHA test and the haemolysis assay were significantly male-biased during breeding, although the latter estimate was obtained only from three effect sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Although data on immune response variables were not available for many species, we did find differences between males and females. The four immune assays analysed reflect innate immunity, except the PHA test that, if repeated more than once, also includes components of the adaptive immunity 85 . The PHA test and the haemolysis assay were significantly male-biased during breeding, although the latter estimate was obtained only from three effect sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, challenges traditionally used in immunoecology are less specific than initially thought and they involve the action of multiple actors. For instance, much effort has been undertaken to understand the effect of PHA on activation of the immune system (Kennedy & Nager, ; Martin et al, ; Santiago‐Quesada et al, ; Tella et al, ). This has revealed a complex action of both innate and acquired immunity, and some authors have even suggested the inappropriateness of PHA tests as a direct proxy of T‐cell responsiveness or adaptive immunity (Vinkler, Bainová, & Albrecht, ).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, it was clear from the results of the CBH test that feeding the birds with 2 ppm AFB1 implies a significant decrease in cellular immunity. The PHA skin test is used to evaluate cellular immunity, since PHA is a potent stimulant that activates immune cells infiltrating tissue from peripheral blood, causing local temporary inflammation at the injection site [ 52 ]. In the present study, AFB1 chickens also showed the lowest response to CBH at both, 12 and 24 h, after PHA injection.…”
Section: Discussionmentioning
confidence: 99%